Lending technologies, firm characteristics and small business efficiency in South Africa - Edson Mbedzi; Munacinga Simatele (Economies, 2022)
Internal factors of Small, Micro and Medium Enterprises (SMMEs) determine their technical efficiency, while external funding characteristics improve the quality of internal factors. Since the type of lending institutions and lending technologies primarily influence the lending decisions of financial institutions, firms' technical efficiency may be linked to such external factors. Literature on determinants of the technical efficiency of SMMEs mainly focuses on internal factors excluding the financial access paradigm which stifles the effectiveness of internal factors on technical efficiency. Based on a sample of 321 randomly selected SMMEs from Eastern Cape Province in South Africa, the study measures technical efficiency using Data Enveloping Analysis and differentiates technical efficiency among firms using Post Hoc Test Pairwise Comparisons derived from factorial ANOVA. Both main and interaction effects were captured in the analysis. Our results, which pinpoint four main findings, show technical efficiency paths followed by firms vary significantly as a result of both internal and external factors. In particular, the effects of other factors are amplified by race. As a consequence, three main contributions emerge from the study.Internal factors of Small, Micro and Medium Enterprises (SMMEs) determine their technical efficiency, while external funding characteristics improve the quality of internal factors. Since the type of lending institutions and lending technologies primarily influence the lending decisions of financial institutions, firms' technical efficiency may be linked to such external factors. Literature on determinants of the technical efficiency of SMMEs mainly focuses on internal factors excluding the financial access paradigm which stifles the effectiveness of internal factors on technical efficiency. Based on a sample of 321 randomly selected SMMEs from Eastern Cape Province in South Africa, the study measures technical efficiency using Data Enveloping Analysis and differentiates technical efficiency among firms using Post Hoc Test Pairwise Comparisons derived from factorial ANOVA. Both main and interaction effects were captured in the analysis. Our results, which pinpoint four main findings, show technical efficiency paths followed by firms vary significantly as a result of both internal and external factors. In particular, the effects of other factors are amplified by race. As a consequence, three main contributions emerge from the study.
Keywords: 330; DEA; factorial ANOVA; lending institution structure; SMME structure; technical efficiency